Cluster identification and characterization in the riser of a circulating fluidized bed from numerical simulation results - Cabezas-Gomez, Luben; da Silva, Renato Cesar; Navarro, Helio Aparecido; Milioli, Fernando Eduardo [UNESP] (Elsevier B.V., 2008)
A methodology of identification and characterization of coherent structures mostly known as clusters is applied to hydrodynamic results of numerical simulation generated for the riser of a circulating fluidized bed. The numerical simulation is performed using the MICEFLOW code, which includes the two-fluids IIT's hydrodynamic model B. The methodology for cluster characterization that is used is based in the determination of four characteristics, related to average life time, average volumetric fraction of solid, existing time fraction and frequency of occurrence. The identification of clusters is performed by applying a criterion related to the time average value of the volumetric solid fraction. A qualitative rather than quantitative analysis is performed mainly owing to the unavailability of operational data used in the considered experiments. Concerning qualitative analysis, the simulation results are in good agreement with literature. Some quantitative comparisons between predictions and experiment were also presented to emphasize the capability of the modeling procedure regarding the analysis of macroscopic scale coherent structures. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: clusters; numerical simulation; gas-solid flow; circulating fluidized bed